PELAYANAN KESEHATAN SAPI DI BANJAR SAMUAN KAWAN DAN SAMUAN KANGIN, DESA CARANGSARI, KECAMATAN PETANG, KABUPATEN BADUNG - SUARDANA, I W AYAN (Buletin Udayana Mengabdi, 2014)
Animal health service is one of key factors to be successful in animal breeding. This program include curativeaction for animal illness, sanitation program and vaccination as a preventive program. Carangsari village especiallySamuan Kawan and Samuan Kangin Sub-villages is potential as one of animal production centrals at BadungRegency, so that the animal health service program is potentially conducted at both places. Results of programshowed the responds of society especially for cattle farmers were very interesting that were identified by so manyanimals were treated by this program i.e. 34 heads (89,5%) treated by vitamins, 21 heads (55,3%) treated by spraying, 7 heads (18,4%) treated by anthelmentics, and 4 heads (10,5%) treated by curative actions. These resultsindicated the animals health service program is helpfully to respond the basic need of animal farmers. Key words : Animals health services, SE, vaccination, spraying, cattle